Bacteria-host transcriptional response during endothelial invasion by Staphylococcus aureus - Rasmus Birkholm Grønnemose; Christian Garde; Claes Søndergaard Wassmann; Janne Kudsk Klitgaard; Ronni Nielsen; Susanne Mandrup; Andreas Holm Mattsson; Thomas Emil Andersen (Scientific Reports, 2021)
Abstract Staphylococcus aureus is the cause of serious vascular infections such as sepsis and endocarditis. These infections are notoriously difficult to treat, and it is believed that the ability of S. aureus to invade endothelial cells and persist intracellularly is a key mechanism for persistence despite ongoing antibiotic treatment. Here, we used dual RNA sequencing to study the simultaneous transcriptional response of S. aureus and human endothelial cells during in vitro infections. We revealed discrete and shared differentially expressed genes for both host and pathogen at the different stages of infection. While the endothelial cells upregulated genes involved in interferon signalling and antigen presentation during late infection, S. aureus downregulated toxin expression while upregulating genes related to iron scavenging. In conclusion, the presented data provide an important resource to facilitate functional investigations into host–pathogen interaction during S. aureus invasive infection and a basis for identifying novel drug target sites.